Patients With Acute Respiratory Distress Syndrome: Value Of Lung Ultrasound (Journal of Pharmaceutical Negative Results, 2023)
Background: When a particular type of lung injury is noted in adversely sick people, it is an acute respiratory distress syndrome (ARDS). ARDS is caused by two different injuries; one is indirect as trauma or in sepsis, and the other one is directly through a lung injury (toxic gas inhalation and pneumonia). The use of lung ultrasound has grown quickly over the years which has a lower specificity and sensitivity.Objective: This research is conducted to study patients who are suffering from acute respiratory distress syndrome and pneumonia and evaluate the value of lung ultrasound as an early investigative technique used for those patients.Study design: A cross-sectional studyPlace and Duration: This study was conducted at GIMS Hospital Gambat from November 2021 to November 2022.Methodology: A total of 60 individuals were a part of this research. All the patients who were enrolled in this research were diagnosed with ARDS and undifferentiated dyspnea. All of the participants underwent a conventional diagnostic workup. Lung ultrasound was performed by trained emergency physicians. To perform lung ultrasound, a low-frequency transducer and curvilinear probe were used. A depth of about 12 centimeters to 18 centimeters was studied. A lung ultrasound was performed to examine 12 lung regions of the chest wall. Those regions were explored by auscultation.Results: A total of 60 patients were a part of this research. There were a total of 38 males, representing 63.3% of the total sample. The number of females was 22, representing 36.7% of the total sample. There were 16 patients in mild, 24 in moderate, and 20 in the severe category of ARDS. All patients in the mild ARDS category had B lines on lung ultrasound. 12 patients had A-lines, representing 75 percent. 4 patients had BB lines, representing 25 percent. Only 2 patients had consolidation, representing 12.5 percent. All patients in the moderate category of ARDS had consolidation. 17 patients had BB lines, representing 70.8%. 13 patients had B lines, representing 54.1%. 12 patients had A-lines representing 50%Conclusion: Lung ultrasound is a useful method in the emergency department with its 4 patterns; A-lines, BB lines, Consolidation, and B-lines.